EFFECT OF HUNGER INDEX ON EDUCATION PERFORMANCE OF SECONDARY SCHOOL GIRL STUDENTS IN MEERUT DISTRICT - Mr. Apar Sharma and Dr (Prof.) Santosh Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The study investigates how the Hunger Index affects the academic achievement of female secondary school pupils in the Meerut district. A major obstacle to learning and academic success is hunger, which is defined by inadequate nutrition and its related impacts. With an emphasis on comprehending how conditions like undernourishment, stunting, and wasting affect cognitive ability and general educational performance, this study examines the relationship between nutritional inadequacies and the academic outcomes of female students in secondary schools. Primary data was gathered through surveys and interviews using a mixed-method approach, while secondary data was added from pertinent studies and reports. The results show differences in academic performance according to nutritional status, with girls from homes with severe or concerning hunger index problems performing worse academically than their classmates. The study highlights the significance of tackling hunger as a crucial factor influencing academic achievement and offers guidance to educators and politicians on how to create focused interventions. It promotes integrated strategies to improve the learning results of female students and encourage fair education in the area, such as better nutrition programs and encouraging learning settings.